2021
DOI: 10.1038/s41598-021-83432-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the predictive value of lesion topology on motor function outcomes in a porcine ischemic stroke model

Abstract: Harnessing the maximum diagnostic potential of magnetic resonance imaging (MRI) by including stroke lesion location in relation to specific structures that are associated with particular functions will likely increase the potential to predict functional deficit type, severity, and recovery in stroke patients. This exploratory study aims to identify key structures lesioned by a middle cerebral artery occlusion (MCAO) that impact stroke recovery and to strengthen the predictive capacity of neuroimaging technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 72 publications
(113 reference statements)
6
12
1
Order By: Relevance
“…This indicates that for functional recovery, lesion topology is more relevant than lesion volume, which again is in line with clinical data. 12,28 It should be noted, that in the 45 minutes MCAO model, lesion volume and lesion topology are not fully independent predictors. Larger ischemic lesions typically include cortical regions while smaller lesions are restricted to subcortical structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that for functional recovery, lesion topology is more relevant than lesion volume, which again is in line with clinical data. 12,28 It should be noted, that in the 45 minutes MCAO model, lesion volume and lesion topology are not fully independent predictors. Larger ischemic lesions typically include cortical regions while smaller lesions are restricted to subcortical structures.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6]8 While one pre-clinical study on predictors of stroke outcome in a porcine MCAO model exists, evidence on prediction of stroke outcome in mice is scarce, despite rodents being used most commonly as model animals in stroke studies. 12,24 We modified previously published protocols for the staircase test of skilled reaching in mice, which enabled us to daily monitor motor function and to detect both subacute and long-term functional deficits. 18,25 Training the mice over a period of 21 days prior to the MCAO surgery and implementing separation during feeding hours enabled us to detect a side-specific disability of the forepaw over a period of three weeks post stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Damage to the corticospinal tract in the putamen would affect lower limb motor function of patients with stroke ( Frenkel-Toledo et al, 2021 ). And ischemic impairment of the putamen was found to be associated with the motor dysfunction in animal ischemic stroke models ( Scheulin et al, 2021 ). In addition, a previous study showed that the low variability of dynamic connectivity between bilateral putamen and the supplementary motor area was related to a better motor recovery of patients with stroke ( Bonkhoff et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%